2020
DOI: 10.1111/fcp.12576
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor antagonist‐mediated cognitive improvement in a mouse model of Alzheimer's type: possible involvement of BDNF‐H2S‐Nrf2 signaling

Abstract: The present study explored the role and mechanisms of mineralocorticoid receptor antagonists in β‐amyloid (Aβ)‐induced cognitive impairment. A single intracerebroventricular injection of Aβ1‐42 was given to mice, and after 14 days of injection, memory was evaluated using the Morris water maze test. Spironolactone (25 and 50 mg/kg) and eplerenone (50 and 100 mg/kg) were administered for two days before and for 14 days after Aβ injection. Mineralocorticoid receptor blockers attenuated Aβ‐induced cognitive impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
0
15
0
1
Order By: Relevance
“…CART treatment improved spatial memory in the MWM task in rats infused with Aβ 1-42 into the hippocampus [93]. Mineralocorticoid receptor antagonists reduced memory impairment in the MWM task in mice with a brain infusion of Aβ 1-42 [94]. Mineralocorticoid receptor antagonists also activated the Nrf2-dependent antioxidant system.…”
Section: The Role Of Nrf2 In Memorymentioning
confidence: 95%
“…CART treatment improved spatial memory in the MWM task in rats infused with Aβ 1-42 into the hippocampus [93]. Mineralocorticoid receptor antagonists reduced memory impairment in the MWM task in mice with a brain infusion of Aβ 1-42 [94]. Mineralocorticoid receptor antagonists also activated the Nrf2-dependent antioxidant system.…”
Section: The Role Of Nrf2 In Memorymentioning
confidence: 95%
“…Studies have shown the function of physiological and pathophysiological roles of H 2 S in the brain including traumatic brain injury 14 , 15 . Furthermore, other studies have pointed out the close interrelationship between H 2 S, neuroinflammation and Nrf2 16 , 17 .…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, it is possible that the Nrf2 system is involved in cognitive decline in multiple diseases [ 222 ]. Nrf2 regulates, among others, the catalytic and modifying subunit of glutamate cysteine ligase (GCL) to increase GSH levels [ 223 ].…”
Section: Methionine Restriction (Mr) Aging and Diseasesmentioning
confidence: 99%